Making a Difference: Evaluating the Girls in the Game (GIG) After-School Program. (January 2013) - Bohnert, Amy M.; Ward, Amanda K.
This randomized controlled trial evaluated the effectiveness of the Girls in the Game (GIG) after-school program (ASP) in promoting social-emotional development and reducing body mass index (BMI) and obesogenic behaviors among a group of minority, low-income girls. Data were collected from 76 third- to fifth-grade girls ( n = 52, GIG; n = 24, controls) from five urban elementary schools prior to and at the conclusion of 30 weeks of programming. Multiple methods were used to assess outcomes and process variables, including questionnaires, observations, and body measurements (i.e., body mass index [BMI]). The program demonstrated high levels of program quality and was well implemented across program sites. Repeated-measures ANOVAs (analyses of variance) revealed small but significant improvements in body image, nutrition knowledge, and behavior for GIG participants. These findings were not moderated by initial levels of self-esteem or BMI. Analyses suggested that program effectiveness varied depending on process variables.